2014
DOI: 10.4049/jimmunol.1300118
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with a Recombinant Bacillus Calmette–Guérin Strain Confers Protective Th1 Immunity against the Human Metapneumovirus

Abstract: Along with the human respiratory syncytial virus (hRSV), the human metapneumovirus (hMPV) is one of the leading causes of childhood hospitalization and a major health burden worldwide. Unfortunately, owing to an inefficient immunological memory, hMPV infection provides limited immune protection against reinfection. Furthermore, hMPV can induce an inadequate Th2 type immune response that causes severe lung inflammation, leading to airway obstruction. Similar to hRSV, it is likely that an effective clearance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 35 publications
(46 reference statements)
3
54
0
Order By: Relevance
“…31 However, this virus also evades these effective anti-viral immune responses. 26 Moreover, na€ ıve BALB/c mice were shown to develop a biphasic immune response in vivo after hMPV infection.…”
Section: Adaptive Immunity Triggered By Hmpvmentioning
confidence: 99%
See 2 more Smart Citations
“…31 However, this virus also evades these effective anti-viral immune responses. 26 Moreover, na€ ıve BALB/c mice were shown to develop a biphasic immune response in vivo after hMPV infection.…”
Section: Adaptive Immunity Triggered By Hmpvmentioning
confidence: 99%
“…[26][27][28][29] The ineffectiveness of the natural infection to induce long-term immunity has hampered vaccine generation and currently there is no licensed vaccine available to prevent the bronchiolitis and pneumonia caused either by hRSV or hMPV. [30][31][32][33][34] However, several candidate vaccines are in different stages of development for preventing the diseases caused by these viral agents. Candidate vaccines for hRSV and hMPV employ different approaches, including a chimeric virus (hMPV), 35 live attenuated virus (hRSV), 36 and purified proteins (hRSV), 37 among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found that recombinant plasmid A3-Vec, like lentivirus delivered A3 (11), could induce A3 fusion protein specific antibody IgG response, indicating that it could be expressed in mice and then recognized by immune system. Moreover, we have observed immunization of plasmid A3-Vec could induce high Th1-type cytokines production, such as IL-2 and TNF-α (22), in spleen lymphocytes in A3-Vec treated mice. Moreover, recombinant plasmid A3-Vec shows potent effective therapeutic effect in acute Mtb infected mice.…”
Section: Discussionmentioning
confidence: 83%
“…Other hMPV proteins which have been used for proteinbased vaccine development include the P and G proteins (Lévy et al, 2013;Palavecino et al, 2014). A recombinant bacillus Calmette-Guerin (a carrier to promote an immune response against antigens from other bacterial, parasitic and viral pathogens) expressing hMPV P protein is able to confer strong effector phenotypes to both CD4 + and CD8 + T cells, which showed protective hMPV immunity equivalent to actively immunized animals.…”
Section: Viral Protein-based Vaccinesmentioning
confidence: 99%